Pharmacokinetics, metabolism and safety of deuterated L‐DOPA (SD‐1077)/carbidopa compared to L‐DOPA/carbidopa following single oral dose administration in healthy subjects. (9th August 2018) - Schneider, Frank; Erisson, Lavi; Beygi, Hooman; Bradbury, Margaret; Cohen‐Barak, Orit; Grachev, Igor D.; Guzy, Serge; Loupe, Pippa S.; Levi, Micha; McDonald, Mirna; Savola, Juha‐Matti; Papapetropoulos, Spyros; et al.
Abstract : Aims: SD‐1077, a selectively deuterated precursor of dopamine (DA) structurally related to L‐3, 4‐dihydroxyphenylalanine (L‐DOPA), is under development for treatment of motor symptoms of Parkinson's disease. Preclinical models have shown slower metabolism of central deuterated DA. The present study investigated the peripheral pharmacokinetics (PK), metabolism and safety of SD‐1077. Methods: Plasma and urine PK of drug and metabolites and safety after a single oral 150 mg SD‐1077 dose were compared to 150 mg L‐DOPA, each in combination with 37.5 mg carbidopa (CD) in a double‐blind, two‐period, crossover study in healthy volunteers ( n  = 16). Results: Geometric least squares mean ratios (GMRs) and 90% confidence intervals (90% CI) of SD‐1077 vs . L‐DOPA for Cmax, AUC0–t, and AUC0–inf were 88.4 (75.9–103.1), 89.5 (84.1–95.3), and 89.6 (84.2–95.4), respectively. Systemic exposure to DA was significantly higher after SD‐1077/CD compared to that after L‐DOPA/CD, with GMRs (90% CI) of 1.8 (1.45–2.24; P  = 0.0005) and 2.06 (1.68–2.52; P  < 0.0001) for Cmax and AUC0–t and a concomitant reduction in the ratio of 3, 4‐dihydroxyphenylacetic acid/DA confirming slower metabolic breakdown of DA by monoamine oxidase (MAO). There were increases in systemic exposures to metabolites of catechol O‐methyltransferase (COMT) reaction, 3‐methoxytyramine (3‐MT) and 3‐O‐methyldopa (3‐OMD) with GMRs (90% CI) for SD‐1077/CD to L‐DOPA/CD for 3‐MT exposure of 1.33 (1.14–1.56; P  = 0.0077) and 1.66 (1.42–1.93; P  < 0.0001) for Cmax and AUC0–t, respectively and GMRs (90% CI) for 3‐OMD of 1.19 (1.15, 1.23; P  < 0.0001) and 1.31 (1.27, 1.36; P  < 0.0001) for Cmax and AUC0–t . SD‐1077/CD exhibited comparable tolerability and safety to L‐DOPA/CD. Conclusions: SD‐1077/CD demonstrated the potential to prolong exposure to central DA at comparable peripheral PK and safety to the reference L‐DOPA/CD combination. A single dose of SD‐1077 is safe for further clinical development in Parkinson's disease patients.